(untitled) (Journal of Kidney Cancer, 2019)
This retrospective study evaluated perioperative outcomes of open partial nephrectomy (OPN), laparoscopic partial nephrectomy (LPN), and robot-assisted partial nephrectomy (RAPN) and identified predictive factors of Trifecta achievement for renal tumors that underwent partial nephrectomy (PN) in a single institutional cohort. The study involved patients who underwent PN from January 2011 to July 2018. Trifecta was defined as absence of perioperative complications, no positive surgical margins, and ischemia time <30 min. Fifty-five PN procedures were reviewed: 28 OPN, 14 LPN, and 13 RAPN. OPN, LPN and RAPN had similar median tumor size (5.75, 5.25, and 5 cm), nephrometry score (7, 6, and 6), and preoperative creatinine (1.09, 1.1, and 1.1 mg/dl, respectively). Blood loss was higher for OPN (550 ml) than for LPN (400 ml) and RAPN (300 ml), P = 0.042. Drain was removed after 6 days in OPN which was higher than LPN and RAPN (4.5 and 4 days, respectively), P = 0.008. OPN, LPN, and RAPN had similar median operative time (190, 180, and 180 min, respectively), P = 0.438. Median postoperative stay for OPN, LPN, and RAPN was 5, 6.5, and 10 days, respectively. Trifecta outcomes of 73.1%, 64.3%, and 61.53% were achieved in OPN, LPN, and RAPN, respectively, P = 0.730. It was concluded that Trifecta outcomes had no significant difference among OPN, LPN, and RAPN. LPN can produce as good results as RAPN. Keeping in mind the cost-effectiveness, LPN holds an important position in developing countries where expenditure by patient is a major factor.